The Continuum of Disclosure: Exploring Factors Predicting Tentative Disclosure of Child Sexual Abuse Allegations During Forensic Interviews and the Implications for Practice, Policy, and Future Research. - Anderson, Gwendolyn D. (Journal of Child Sexual Abuse)
When a child sexual abuse investigation ensues, many children do not disclose readily to professionals. Defining disclosure beyond the disclosure versus nondisclosure dichotomy is essential, yet little research exists on factors associated with a continuum of disclosure, including active and tentative disclosure. Through the coding of 196 forensic interviews using content analysis and subsequent regression analysis, findings suggest that children of color, children abused by adults, unintentional initial disclosure, and those lacking family support were more likely to tentatively disclose in this study. Implications include a need to understand tentative disclosure as part of a normal continuum of disclosure within court proceedings and investigations of abuse allegations.